ANALYZE THE EFFECT OF VISUAL MERCHANDISING AND BRAND IMAGE ON CUSTOMER PURCHASE INTENTION CASE STUDY: STARBUCKS CUSTOMER IN MANADO CITY - Fabio Falentino Kamu; James D. D. Massie; Ferdinand J. Tumewu (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
This research aims to analyze the effect of visual merchandising, and brand image on customer purchase intention at Starbucks Customer in Manado. The independent variables used in this research are visual merchandising and brand image, while the dependent variable is purchase intention. This research uses primary data obtained from questionnaires measured with the Likert Scale. The sample is customer who have shopped in Starbucks Manado. Test instruments are performed usingV alidity and Reliability Tests. The regression result show that visual merchandising and brand image have a positive and significant effect on purchase intention through Starbucks Manado.   Keyword: visual merchandising, brand image, purchase intention